2019
DOI: 10.32615/bp.2019.065
|View full text |Cite
|
Sign up to set email alerts
|

Effects of various winter chilling regimes on flowering quality indicatorsof Greek olive cultivars

Abstract: Aims of the present two-year study were to evaluate the feasibility and identify potential drawbacks of the greenhouse/ outdoors parallel plant growth methods for investigation of the effects of various winter chilling regimes on flowering quality indicators of four Greek olive cultivars, namely Mastoidis, Amfissis, and Lefkolia Serron (originating from mountainous and colder areas) compared to cv. Koroneiki (grown mainly in plain warm areas). Groups of potted olive plants were either grown outdoors under ambi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 38 publications
1
6
0
Order By: Relevance
“…This extremely low chill accumulation may not prove adequate for the induction of flowering in Koroneiki or other olive cultivars of similar temperature adaptations. Koroneiki olive cultivar has also been the subject of other research studies in relation to its suitability in projected climate scenarios (Gabaldón-Leal et al 2017;Koubouris et al 2019). In comparison, the present study appears to have a higher value as our analyses are based on field observations up to 31 years, whereas the above two studies consist of experimentation on potted plants, including outdoor and greenhouse treatments for a limited time.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…This extremely low chill accumulation may not prove adequate for the induction of flowering in Koroneiki or other olive cultivars of similar temperature adaptations. Koroneiki olive cultivar has also been the subject of other research studies in relation to its suitability in projected climate scenarios (Gabaldón-Leal et al 2017;Koubouris et al 2019). In comparison, the present study appears to have a higher value as our analyses are based on field observations up to 31 years, whereas the above two studies consist of experimentation on potted plants, including outdoor and greenhouse treatments for a limited time.…”
Section: Discussionmentioning
confidence: 80%
“…Olive cultivar genotype and its local adaptation define thermal requisites whereas latitude, longitude, and elevation are among the most important factors that modulate the fulfillment of the thermal requisites of the olive tree (Aguilera et al 2014;Rojo et al 2020), although, so far, tree chill and heat needs generally have not been reliably quantified (Chuine et al 2016;Lorite et al 2020). A number of studies have linked changes in the chilling process with impacts on the quantity and quality of flowering that subsequently may affect olive production (Torres et al 2017;Koubouris et al 2019;Benlloch-González et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Olive cultivars differ in chilling requirements between low chilling requirements like 'Koroneiki' and high like 'Sevillano' (Aybar et al, 2015;Malik and Bradford, 2006). Koubouris et al (2019) reported a decrease in the number of flowers/inflorescences in Greek olive cultivars 'Koroneiki' and 'Mastoides' resulted from low chilling, while no effect was found on inflorescence length or width. Any way the threshold used in calculating chilling requirements differed among authors, where some used 7.2°C (Hartmann and Porlinglis, 1957;Zouari et al 2017), while others used 9, 10, 12.5, 15 and/ or 16°C (Alcalá and Barranco, 1992;Haberman et al, 2017;Selak et al, 2018;Koubouris et al, 2019).…”
Section: Introductionmentioning
confidence: 96%
“…Koubouris et al (2019) reported a decrease in the number of flowers/inflorescences in Greek olive cultivars 'Koroneiki' and 'Mastoides' resulted from low chilling, while no effect was found on inflorescence length or width. Any way the threshold used in calculating chilling requirements differed among authors, where some used 7.2°C (Hartmann and Porlinglis, 1957;Zouari et al 2017), while others used 9, 10, 12.5, 15 and/ or 16°C (Alcalá and Barranco, 1992;Haberman et al, 2017;Selak et al, 2018;Koubouris et al, 2019). Other studies reported different thresholds depending on latitude, so thresholds are lower in olive orchards located at higher latitudes (Aguilera et al, 2014).…”
Section: Introductionmentioning
confidence: 96%
“…Climatic conditions, in general, play a decisive role in tree phenology and adaptation [29]. Temperature during spring is considered to have great effect on olive flower development [30], pollen germination [31], fruit set and development [5] as well as the number of flowers per panicle [32]. In addition, temperature levels as low as 0 • C may cause drastic damages on flower buds and flowers [33].…”
Section: Introductionmentioning
confidence: 99%